Study the effect of value-added of services sector on forecasting of electricity demand in services sector due to price reform - Sayed Mahdi Mostafavi; Saeed Shoauri; Seyyed Mohammad Seyyed Hosseini (Atlantic Review of Economics, 2016)
Electrical energy is as one of the important effective factors on economic growth and development. In recent decades, numerous studies in different countries to estimate and forecast electricity demand in different parts of the economy have been made. In this paper, using the method ARDL, estimation and forecasting of electricity demand in the services sector of Iran are determined for the time period from 1983 to 2012. Estimated equations show that the added value of the services sector and a significant positive impact on the demand for electricity in this sector.The price elasticity for services sector is smaller than 1 due to low electricity prices and subsidized electricity. Hence, electricity prices have little impact on the demand for electricity. The results of the estimate represents a long-term relationship between the variables in the services sector. In this paper, based on amendments to the law on subsidies and estimated values, anticipated electricity demand until the end of the fifth development plan was carried out. The results indicate an increase in power consumption in the services sector.
Keywords: Q31; E64; L16; C32; 330; electricity; value-added; ARDL; Services sector; Price reform